Advancing Healthcare Reform: The American Heart Association's 2020 Statement of Principles for Adequate, Accessible, and Affordable Health Care. Issue 10 (10th March 2020) - Warner, John J.; Benjamin, Ivor J.; Churchwell, Keith; Firestone, Grace; Gardner, Timothy J.; Johnson, Janay C.; Ng-Osorio, Jackie; Rodriguez, Carlos J.; Todman, Lynn; Yaffe, Kristine; Yancy, Clyde W.; Harrington, Robert A.
Abstract : The mission of the American Heart Association is to be a relentless force for a world of longer, healthier lives. The American Heart Association has consistently prioritized the needs and perspective of the patient in taking positions on healthcare reform while recognizing the importance of biomedical research, providers, and healthcare delivery systems in advancing the care of patients and the prevention of disease. The American Heart Association's vision for healthcare reform describes the foundational changes needed for the health system to serve the best interests of patients and to achieve health care and coverage that are adequate, accessible, and affordable for everyone living in the United States. The American Heart Association is committed to advancing the dialogue around healthcare reform and has prepared this updated statement of our principles, placed in the context of the advances in coverage and care that have occurred after the passage of the Affordable Care Act, the rapidly changing landscape of healthcare delivery systems, and our evolving recognition that efforts to prevent cardiovascular disease can have synergistic benefit in preventing other diseases and improving overall well-being. These updated principles focus on expanding access to affordable health care and coverage; enhancing the availability of evidence-based preventive services; eliminating disparities that limit the availability and equitable delivery of health care; strengthening the public health infrastructure to respond to social determinants of health; prioritizing and accelerating investments in biomedical research; and growing a diverse, culturally competent health and healthcare workforce prepared to meet the challenges of delivering high-value health care.